Specificity and Function of Archaeal DNA Replication Initiator Proteins - Samson, Rachel Y. (Cell Press, 2013)
Chromosomes with multiple DNA replication origins are a hallmark of Eukaryotes and some Archaea. All eukaryal nuclear replication origins are defined by the origin recognition complex (ORC) that recruits the replicative helicase MCM(2-7) via Cdc6 and Cdt1. We find that the three origins in the single chromosome of the archaeon Sulfolobus islandicus are specified by distinct initiation factors. While two origins are dependent on archaeal homologs of eukaryal Orc1 and Cdc6, the third origin is instead reliant on an archaeal Cdt1 homolog. We exploit the nonessential nature of the orc1-1 gene to investigate the role of ATP binding and hydrolysis in initiator function in vivo and in vitro. We find that the ATP-bound form of Orc1-1 is proficient for replication and implicates hydrolysis of ATP in downregulation of origin activity. Finally, we reveal that ATP and DNA binding by Orc1-1 remodels the protein’s structure rather than that of the DNA template.